2005
DOI: 10.1542/peds.2004-2785
|View full text |Cite
|
Sign up to set email alerts
|

Early Respiratory Infections, Asthma, and Allergy: 10-Year Follow-up of the Oslo Birth Cohort

Abstract: ABSTRACT. Objective. It has been hypothesized that early infections protect against the development of atopic disease, but there have been few long-term follow-up studies. We estimated the associations between early respiratory infections and doctor-diagnosed asthma, allergic rhinitis, and skin-prick sensitization in children at 10 years of age in the Oslo Birth Cohort, established in 1992-1993. We also considered birth order and attendance at a child care center as proxy measures of increased exposure to infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
69
2
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 48 publications
6
69
2
7
Order By: Relevance
“…In the TCRS, this association was found to be confounded by maternal asthma. [9,57] There was lack of agreement with regards to the association of day-care with persistent wheeze, with ALSPAC finding that day-care was associated with an increase in persistent wheeze [36], TCRS finding that day-care was protective [27]. Similarly, ALSPAC identified a significant positive association between persistent wheeze and number of older siblings [32,36], whereas TCRS found that this was the only wheeze phenotype where the presence of older siblings reduced the risk of persistent wheeze [27].…”
Section: Early Life Wheeze (Transient and Prolonged)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the TCRS, this association was found to be confounded by maternal asthma. [9,57] There was lack of agreement with regards to the association of day-care with persistent wheeze, with ALSPAC finding that day-care was associated with an increase in persistent wheeze [36], TCRS finding that day-care was protective [27]. Similarly, ALSPAC identified a significant positive association between persistent wheeze and number of older siblings [32,36], whereas TCRS found that this was the only wheeze phenotype where the presence of older siblings reduced the risk of persistent wheeze [27].…”
Section: Early Life Wheeze (Transient and Prolonged)mentioning
confidence: 99%
“…An example of an inconsistent association with asthma is day-care attendance. Different studies have indicated that day-care attendance increases the risk [7], is protective [8] and has no effect [9] on the development of asthma. It is likely that imprecise phenotype definition together with the failure to take account of interactions between the environment and genetic predispositions (day care -TLR2, endotoxin -CD14 being but two examples) [10][11][12] have hampered our attempts to 'explain' asthma.…”
Section: Introductionmentioning
confidence: 99%
“…4S. 4 All appropriate isotype controls were used (BD Biosciences). Abs were titrated to determine optimal concentration.…”
Section: Lung Cell Isolation and Flow Cytometric Analysis Of Lung Cellsmentioning
confidence: 99%
“…A growing number of epidemiologic studies have shown that certain respiratory viral infections in infancy are associated with increased atopy to common allergens and an overall increased risk of asthma in school-aged children (4,5). Such an outcome seems intuitive in the case of infections with respiratory syncytial virus (RSV) which induces Th2-polarized immunity (6,7) and can, thereby, establish a lung environment that facilitates subsequent sensitization to allergens.…”
mentioning
confidence: 99%
“…), и потому не была установлена причинно-следственная связь. Более того, такое воздействие различно у разных вирусов [1][2][3][4][5][6].…”
unclassified